(untitled) (Journal of Statistical Research, 2026)
This paper investigates the conditional hazard function of a scalar response variable given a predictor that takes values in a semi-metric space. We employ a local linear estimator for the conditional density and cumulative distribution function, and establish almost sure convergence rates under α-mixing dependence. The analysis is conducted under a set of regularity conditions for the proposed estimator. Furthermore, the practical relevance of the theoretical results is demonstrated through a simulation study. Journal of Statistical Research 2025, Vol. 59, No. 2, pp. 259-278